Nonalcoholic steatohepatitis and gut microbiota: Future perspectives on probiotics in metabolic liver diseases - Yusuf Yılmaz,; Fatih Eren, (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Yılmaz Y, Eren F. Nonalcoholic steatohepatitis and gut microbiota: Future perspectives on probiotics in metabolic liver diseases. Turk J Gastroenterol 2017; 28: 327-8